A dimensão conceitual da organização do conhecimento no universo científico da ISKO: uma análise de domínio a partir dos congressos da ISKO-Brasil, ISKO-Espanha, ISKO-América Do Norte e ISKO-França: La dimensión conceptual de la organización del conocimiento en el universo cientíifico de la ISKO: un análisis de dominio de los congresos de ISKO-Brasil, ISKO-España, ISKO-Norteamerica e ISKO-Francia - Guimarães, José Augusto Chaves [UNESP]; De Matos, Daniela Fernanda Oliveira [UNESP]; Dos Santos, André Ynada [UNESP]; De Sales, Rodrigo (My University, 2015)
We comparatively analyze the conceptual question of knowledge organization and the theoretical references that are fundamental in the last two Brazilian, Spanish, North American and French ISKO chapter meetings (of 2011 and 2013). From this, we conducted content analysis and citation analysis. The results show that the four analyzed chapters are quite fruitful in addressing conceptual issues, even when this aspect is still in development. This is verified by, on one hand, the concern with aspects such as the nature and object of knowledge organization in its epistemological configuration, and on the other hand, a more pragmatic and operational interest related to knowledge organization processes and tools, sometimes perceived as field objects. In this context, the main theoretical references involve seven authors (Hjørland, Dahlberg, Gardin, Mai, Olson, Barité and Thelleffssen). Hjørland and Dahlberg assume strong leaderships that show, respectively, the emphasis of social-cognitive and ontological approaches in the area. The emphasis of social-cognitive seems to take a greater force especially with Mai and Thelleffssen, with the semiotic question, and Olson, with cultural studies, that reinforce this theoretical framework.
The conceptual dimension of knowledge organization in the scientific universe of ISKO: A domain-analysis of ISKO-Brazil, ISKO-Spain, NASKO and ISKO France conferences
Keywords: Brazil; Concept; Content analysis; Domain analysis; France; International Society for Knowledge Organization; ISKO; Knowledge organization; North America; Spain